2010
DOI: 10.1016/j.carres.2010.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced stereoselectivity of α-mannosylation under thermodynamic control using trichloroacetimidates

Abstract: O-Specific polysaccharides of Vibrio cholerae O1, serotype Inaba and Ogawa, consist of α-(1→2)-linked N-(3-deoxy-L-glycero-tetronyl)perosamine (4-amino-4,6-dideoxy-D-mannose). The blockwise synthesis of larger fragments of such O-PSs involves oligosaccharide glycosyl donors that contain a nonparticipating 2-O-glycosyl group at the position vicinal to the anomeric center where the new glycosidic linkage is formed. Such glycosyl donors may bear at C-4 either a latent acylamino (e.g. azido) or the 3-deoxy-L-glyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…The known [ 8 ] trichloroacetimidate 1 was used as a glycosyl donor to couple with methyl 6-hydroxyhexanoate [ 9 ] under trimethylsilyl trifluoromethanesulfonate (TMSOTf) catalysis. Only αglycoside 2 was formed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The known [ 8 ] trichloroacetimidate 1 was used as a glycosyl donor to couple with methyl 6-hydroxyhexanoate [ 9 ] under trimethylsilyl trifluoromethanesulfonate (TMSOTf) catalysis. Only αglycoside 2 was formed.…”
Section: Resultsmentioning
confidence: 99%
“…5-(Methoxycarbonyl)pentyl-3-O-benzyl-4-(2,4-di-O-acetyl-3-deoxy- l -glycero-tetronamido)-4,6-dideoxy-2-O-levulinoyl-α- d -mannopyranoside ( 2 ). A mixture of Compound 1 (5.7 g, 8.36 mmol) [ 8 ], methyl 6-hydroxyhexanoate [ 9 ] (1.34 g, 9.19 mmol) and 4 Å MS (1.0 g) in CH 2 Cl 2 (anhydrous) was stirred at room temperature under Ar for 30 min. TMSOTf (83 μL, 0.46 mmol) was added, and the mixture was stirred for another 5 h. TLC ( R f = 0.3, EtOAc–hexane 1:1) showed that all of 1 was consumed and that a slightly more polar product was formed.…”
Section: Methodsmentioning
confidence: 99%
“…Thioglycoside 7 gave direct access to hemiacetal 11 and subsequently imidate 12 , which was used to glycosylate the six carbon linker 13 12b. Better yields and selectivity in the preparation of 14 were obtained by performing the reaction in toluene at 100 °C 17. Transesterification of 14 gave the tether glycoside acceptor 15 (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of nonasaccharide 2 was envisaged as the creation of a pentasaccharide donor terminated by a 1,3 linkage which would then allow for a pentasaccharide donor with a participating group at C‐2 to guide the stereoselective α‐glycosylation of an exclusively 1,2‐linked tetrasaccharide. To achieve the synthesis of the pentasaccharide donor, compound 7 was deprotected to give the corresponding acceptor 20 , which was glycosylated by imidate donor 12 as described for 14 17. Tetrasaccharide thioglycoside 21 was used directly as the donor for glycosylation of the monosaccharide glycoside 6 to give the α1,3‐linkage.…”
Section: Methodsmentioning
confidence: 99%
“…We have been involved in the synthesis of oligosaccharides that mimic the structure of O-PS and the use thereof as components of a conjugate vaccine for cholera caused by Vibrio cholerae O1 for a number of years. [5][6][7][8][9] The O-antigen of V. cholerae O139 is 10 a hexasaccharide consisting of D-quinovosamine, D-galacturonic acid, Dglucosamine, D-galactose, and two L-colitose moieties. A 4,6-O-cyclic phosphate residue is attached to the galac-tose unit.…”
mentioning
confidence: 99%